When trade meets tradition : Unpacking cultural differences and their impact on China’s international trade - Yu, Bin; Zhong, Xingyu; Ghimire, Binam; Sapkota, Niranjan (Elsevier, 2025)
Amidst renewed trade tensions and heightened uncertainty in global financial markets, this paper examines the impact of cultural differences on China’s international trade. Departing from majority of prior studies treating cultural disparities as static, we employ dynamic models to capture cultural differences over 2001–2021 with its 44 key trading partners. We incorporate Hofstede’s six cultural dimensions and apply both linear and non-linear models. Our findings show a consistent negative effect of cultural distance on China’s trade. The non-linear analysis uncovers a S-shaped curve relationship, highlighting the subtle influence of cultural differences confirmed by robustness tests in export and import trades. We argue that the impact of trade tensions can be lessened by aligning with the evolving nature of consumer preferences and psychological factors.
Keywords: China; Consumer preferences; Consumer psychology; Cultural distance; Gravity model; Poisson pseudo maximum likelihood; Trade; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|